The Place of Probability in Science In Honor of Ellery Eells (1953-2006) - Eells, Ellery; Fetzer, J.H.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
The purpose of philosophy, broadly conceived, can be described as that of attempting to resolve heretofore unsolved conceptual and theoretical problems, especially those that lie at the foundations of knowledge and values. Given the central role of science in acquiring reliable knowledge, the study of science has become of special importance within philosophy. And within philosophy of science, in turn, no other concept possesses the centrality and importance as does that of probability. To clarify and illuminate the place of probability in science Ellery Eells and James H. Fetzer have brought together some of the most distinguished philosophers from our time. After a comprehensive introduction to alternative conceptions of objective probability and the difficulties that they confront, three studies describe the special problems that arise within this context and the comparative merits of different accounts. The second section addresses the nature of lawfulness and of relations between micro- and macro-probabilities, especially with reference to the concept of fitness in evolution. The third section confronts some of the difficulties confronted by causal conceptions of probability, especially within the quantum domain. The fourth extends the discussion to principles of inference and decision. The last chapter relates propensities and frequencies to the framework of inference to the best explanation.
ALTERNATIVE CONCEPTIONS OF PROBABILITY -- Probabilistic Causality and Causal Generalizations -- Probabilistic Causality and Causal Generalizations -- The Possibility of Infinitesimal Chances -- Probabilistic Metaphysics -- THE OBJECTIVITY OF MACRO-PROBABILITIES -- Chance and Necessity -- Evolutionary Theory and the Reality of Macro-Probabilities -- Is Evolution An Optimizing Process? -- PROBABILITIES AS EXPLANATORY PROPERTIES -- Propensity Trajectories, Preemption, and the Identity of Events -- Miraculous Consilience of Quantum Mechanics -- Probability and Objectivity in Deterministic and Indeterministic Situations -- PROBABILITIES IN INFERENCE AND DECISION -- How Bayesian Confirmation Theory Handles the Paradox of the Ravens -- Learning to Network -- Probabilities in Decision Rules -- Propensities and Frequencies.
Keywords: Philosophy (General).; Genetic epistemology; Philosophy, modern; Science -- Philosophy; Social sciences -- Philosophy; Mathematical statistics; Philosophy; Philosophy of Science; Epistemology; Statistical Theory and Methods; Philosophy of the Social Sciences; Modern Philosophy